Nonuniform compensation of current density distribution in polymer electrolyte fuel cells by local heating - Zhou, S; Rasha, L; Xu, L; Du, W; Shearing, PR; Coppens, M-O; Brett, DJL; Jervis, R (Elsevier, 2023)
A homogeneous current density distribution improves a fuel cell's performance and prolongs its service life. Effective cell structure designs and uniform compression during assembly could support this goal by ensuring a homogeneous reaction rate across the activation area. Due to the coupling of hydro-electro-thermal relationships, for instance, the concentration of reactants along the flow field decreases continuously as the electrochemical reaction proceeds, and the subsequent accumulation of liquid water leads to a low current density at the outlet. The effect of operating conditions, such as local heating, on the current density distribution requires further investigation. This paper studies the impact of local heating on polymer electrolyte fuel cell (PEFC) performance and analyses the effects on voltage by mapping the current density distribution across the active area. Local heating was supplied to the three regions of the electrode, namely, fuel inlet, central and outlet regions, with the latter exhibiting the best performance (in the activation, Ohmic and mass transport controlled region, the output voltage increases compared to no local heating corresponding to 1.28%, 2.17% and 2.46%, respectively). Here, we show that in all local heating cases, outlet heating can compensate for the lowest current density region with the largest current density increased by 91.10 mA cm−2 and achieves a more homogeneous current distribution, while inlet heating aggravates heterogeneity. This study provides practical guidance for optimal thermal management system development whereby the cooling channel design should be locally optimised for more uniform distributions of current density and temperature compared to heating the cell uniformly.